A 206-nm all-solid-state deep-ultraviolet laser with 291 MW peak power - Ran, Qiandong; Short, Joel Stephen; Wang, Qi Jie; Li, Hao (Frontiers in Physics, 2023)
We successfully demonstrate the generation of an all-solid-state deep-ultraviolet (DUV) laser at 206 nm through the 5th (4+1) harmonic generation using a 197 W, 10 kHz 1.2 ps 1030 nm Yb:YAG laser. The DUV laser delivers 180 µJ 582 fs pulses with a peak power of 291 MW, which, to the best of our knowledge, is the highest peak power at 206 nm ever produced by all-solid-sate DUV laser sources driven at 1 um wavelength. This corresponds to a single order improvement from early state-of-the-art record reported in literature.